The Effect of Activated Growth Factor (AGF) from Platelets on Alpha-SMA Levels in Osteoarthritis: Invivo Study - Ziske Maritska; Hidayat, Rachmat; Septi Purnamasari; Muhammad Rizky Hidayatullah; Sarah; Najla Khairunnisa (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: The most prevalent joint condition and leading contributor to disability is osteoarthritis (OA), resulting in a significant socio-economic impact. It occurs due to an imbalance of pro-inflammatory and anti-inflammatory mediators, influencing anabolic and catabolic activities. This study aims to determine the effect of activated growth factor (AGF) on alpha-SMA levels. Methods: This research is an in vivo post-test-only control group experimental study conducted at the Eureka Research Laboratory. Thirty male Wistar rats were divided into five treatment groups: normal control group, negative control group, AGF I group (TGF-β 100 pg/mL), AGF II group (TGF-β 1000 pg/mL), and AGF III group (TGF-β 10,000 pg/mL). AGF was obtained from rat blood intravenously and centrifuged at a predetermined speed. Growth factor activation was performed by adding 10% CaCl2, and then TGF-β levels were measured. All groups of rats were acclimatized for 7 days. After that, osteoarthritis was induced with intra-articular injection of monoiodoacetate (MIA) 4.8 mg/60μL in all groups of rats except the normal control group. Next, rats were given treatment according to the group for 21 days. On the 21st day, rats were euthanized, and alpha-SMA levels were measured using the sandwich method ELISA kit. Results: Sequentially, the mean Alpha-SMA levels for each group in pg/mL were: 91.495 ± 2.36; 10.682 ± 1.09; 30.502 ± 2.00; 52.892 ± 1.29; and 76.180 ± 2.65. In the AGF group, there was an increase in alpha-SMA levels directly proportional to the dose of TGF-β injected. Conclusion: AGF has an effect on increasing alpha-SMA levels in the joints of rats with a model of osteoarthritis.